OC-161 Investigation of the action of histone deacetylase inhibitors in ex vivo and in vitro models of inflammatory bowel disease. (28th May 2012) - Edwards, A J P; Gwiggner, M; Claridge, A G; Morgan-Walsh, R J; Hayden, A L; Bateman, A; Cummings, J R F; Packham, G K; Pender, S L F
Abstract : Introduction: The management of inflammatory bowel disease (IBD) has evolved rapidly with anti-TNFα agents and the more appropriate use of immunomodulators. Despite this, a large therapeutic gap remains to be filled. Histone deacetylase (HDAC) inhibitors (HDI) preserve acetylation of core histones which prevents chromatin from condensing thus facilitating gene transcription. HDI have been approved for the treatment of sub-cutaneous T-cell lymphoma and recent work has shown that HDI may have a protective anti-inflammatory effect in murine models of UC (Tao et al 2007). We hypothesise that HDI have anti-inflammatory effects in human IBD and aim to investigate this using a human ex vivo model of IBD. Methods: Carefully phenotyped patients with active UC (n=7) and CD (n=10) undergoing lower GI endoscopy had 8 pinch biopsies (≈3 mm 2 ) taken for these experiments. Biopsies were cultured ex vivo at an air liquid interface for 8 h±FK228 or SAHA. Additionally, gut fibroblasts isolated from resection tissue were used to model mucosal plasticity in vitro±TNF-α and FK228 and a monocytic cell line (U937) was differentiated in vitro with GMCSF±FK228. Supernatants, RNA and tissue were collected for analysis by qRT-PCR, mesoscale assay, western blotting and histology. Results: Nanomolar levels of FK228 significantly reduce mRNA expression and protein secretion of Th1 and Th2 cytokines and pro-inflammatory mediators (IL-8, MMP-1, -3, -9 and -12) in the ex vivo UC and CD biopsy models. Data suggest that FK228 can decrease mRNA expression of Th1 and Th17 signalling molecules in the ex vivo models. FK228 significantly decreases IL-8, MMP-3 and MMP-12 mRNA expression as well as IL-8 and MMP-3 protein secretion by gut fibroblasts and decreases GMCSF induced MMP-12 protein production by U937 cells. Conclusion: This human ex vivo biopsy culture model is relevant for pre-clinical study of drug action in IBD as it utilises small amounts of tissue in a human system. FK228 produces significant anti-inflammatory effects at low doses by reducing cytokines and MMPs in this model. FK228 is able to act upon specific cells found in the gut such as lymphocytes, fibroblasts and monocytes to elicit anti-inflammatory effects. Based upon our initial findings, further investigation of the role of FK228 in IBD is warranted. Competing interests: None declared.